Sunday

April 20, 2014

April 20, 2014

Posted by **tayaqua** on Wednesday, June 20, 2012 at 11:54pm.

- math -
**Katie**, Thursday, June 21, 2012 at 12:15am4p + 9 + (-7p) +2

= 4p -7p + 9 + 2

= -3p +11

= 11-3p

**Related Questions**

math - Which of the following is not a polynomial ? [A] x0 [B] x+y2 +3z -1+5a [C...

algebra - Provide A Reason For Each Step Of Simplifying The Expression 3 3(4p-1...

MATH - 0.4P+1=0.7P-2 IS IT 3

math - help me solve this 4p+5-7p=-1

math - 7p-6+4p=-39

Math - For the given problem simplify the expression. 1. 4d - 5 - 9d + 17 2.-8p...

maths - how do you simplify this expression 8p-p-4p

equations & inequalities - 1.simplify this expression 4p+9+(-7p)+2=? a.3p+11 b....

math - application of the laws of exponent. show different ways of simplifying ...

Math - Which expression represents the number in the pattern where "p" is the ...